Flow induced trading by active and indexed funds: stock share return predictability in Brazil - Cunha, Aline Helena Azevedo (2015)
The paper intends to analyze the impact of active and indexed funds’ expected future flows in the return of the stock shares they hold. In order to do so, we built a variable that takes in account how the funds respond to new flows, regarding the transaction of shares, and the expected flow, separating funds classified as Pure Indexing, Closet Indexed and Stock Picking. The results show that the variable helps to explain shares’ return especially in holding periods of four, five and six months. We also built long-short portfolios considering the output of the model and the results show that they perform better than the risk free benchmark in the most part of the period.